Synthesis and Characterization of αFe2O4/g-C3N4 Materials for Treatment of Congo Red Dye in Water - Trang, Pham Huynh Thanh; Trieu, Nguyen Hai; Trang, Nguyen Thi; Nham, Nguyen Thi; Viet, Nguyen Minh (VNU Journal of Science: Natural Sciences and Technology; Vol 39 No 2DO - 10.25073/2588-1140/vnunst.5512, 2023)
In recent years, the problem of environmental pollution is becoming extremely serious. Especially, environmental pollution caused by textile dyes not only affects living organisms in the water but also affects human health. There are many methods applied to remove dyes in water; in which, photocatalysis has been proven to be an efficient method. The g-C 3 N 4 is a polymer material with small bandgap energy (about 2,7 eV) as well as chemical and thermal stability in the ambient environment. In this study, the g-C 3 N 4 material was successfully synthesized from urea calcined at 550 0 C, and the modified materials αFe 2 O 3 /g-C 3 N 4 were also successfully prepared by hydrothermal method. The synthesized materials were characterized by modern analytical techniques, such as SEM-EDX, XRD, UV-Vis, and FT-IR. The experimental results showed that synthesized materials have high efficiency in removing Congo Red dye in water under visible light irradiation. Especially, the 7% αFe 2 O 3 /g-C 3 N 4 material had the best efficiency of Congo Red treatment, with an efficiency of up to 93.59% at pH 5 after 150 minutes.